Budaya, Kepribadian, Sosial, Psikologi Berpengaruh pada Perilaku Pemilihan Lokasi Café pada Konsumen Penikmat Kopi - Enggal Sriwardiningsih; Budiman Notoatmodjo (STIE Indonesia Banking School, 2019)
The purpose of this study examined the consumer behavior of coffee connoisseurs after a visit to a shop or café. This study also aims to analyze what factors influence them visiting the café. The researcher distin-guished two groups of types of places. Are there differences in consumer behavior towards the two types, Café type 1 refers to foreign ownership of the example of The Starbuck café and The Bean café. Café type 2 refers to domestic ownership such as The Excelso cafe, The X-Café, The JCo, The KFC and the Warteg. Factors observed in consumers are cultural, social, personality and psychological variables. The number of visitor respondents is not known with certainty, so convenience sampling is used with the number of re-spondents as many as 200 people in the community of staff, campus lecturers and students of Binus Uni-versity. The analytical tool used is SmartPls version 3. The results of this study indicate that cultural, per-sonality and social variables have a significant effect on consumer site selection behavior. Consumer be-havior visits the location of a larger type 2 café (local ownership) rather than type 1 (foreign ownership). The larger type 2, it is probable that positive perceptions of name, equality and price are unfortunately, but it not examined in this study. The end of the study included suggestions for further researchers.